Attention to the body depends on eye-in-orbit position - Gherri, Elena; Forster, Bettina (Frontiers in Psychology, 2014)
Attentional selectivity in touch is modulated by the position of the body in external space. For instance, during endogenous attention tasks in which tactile stimuli are presented to the hands, the effect of attention is reduced when the hands are placed far apart than when they are close together and when the hands are crossed as compared to when they are placed in their anatomical position. This suggests that both somatotopic and external spatial reference frames coding the hands’ locations contribute to the spatial selection of the relevant hand. Here we investigate whether tactile selection of hands is also modulated by the position of other body parts, not directly involved in tactile perception, such as eye-in-orbit (gaze direction). We asked participants to perform the same sustained tactile attention task while gazing laterally towards an eccentric fixation point (Eccentric Gaze) or towards a central fixation point (Central Gaze). SEPs recorded in response to tactile non-target stimuli presented to the attended or unattended hand were compared as a function of gaze direction (Eccentric vs. Central conditions). Results revealed that attentional modulations were reduced in the Eccentric gaze condition as compared to the Central gaze condition in the time range of the Nd component (200-260 ms post-stimulus), demonstrating for the first time that the attentional selection of one of the hands is affected by the position of the eye in the orbit. Directing the eyes towards an eccentric position might be sufficient to create a misalignment between external and somatotopic frames of references reducing tactile attention. This suggests that the eye-in-orbit position contributes to the spatial selection of the task relevant body part.